Islamic Understanding of Feminism and Gender: Between Tradition and the Pressures of the Age: (Pemahaman Islam tentang Feminisme dan Gender: Antara Tradisi dan Tekanan Zaman) - Abdul Bari; Hasan Muhammad Alfatih; Asep Abdul Muhyi (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Islamic understanding of feminism and gender is a complex and relevant subject in the current global context. This article aims to explore Islamic views on feminism and gender as well as an attempt to find a meeting point between Islamic values and aspirations for gender equality in the context of traditions and the demands of the times that continue to develop. Through literature searches and concept analysis, this article highlights the differences and similarities between Islamic views and modern feminism regarding women's rights, gender construction, and the role of women in society. In addition, this article also illustrates how Islamic views on feminism reflect the complex dynamics between diverse religious values, cultures and social contexts throughout the world. By paying attention to this complexity, this article emphasizes the importance of intercultural and interreligious dialogue in fighting for gender equality in a holistic and inclusive manner. It is anticipated that this article will provide deeper insight into feminism and gender in an Islamic context, as well as encourage readers to engage in ongoing and in-depth discussions about these issues in an increasingly connected global society.